2015
DOI: 10.3390/ijerph121012127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Improved Water Supply on Diarrhea Prevalence of Children under Five in the Volta Region of Ghana: A Cluster-Randomized Controlled Trial

Abstract: Although a number of studies have been conducted to explore the effect of water quality improvement, the majority of them have focused mainly on point-of-use water treatment, and the studies investigating the effect of improved water supply have been based on observational or inadequately randomized trials. We report the results of a matched cluster randomized trial investigating the effect of improved water supply on diarrheal prevalence of children under five living in rural areas of the Volta Region in Ghan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
(31 reference statements)
0
24
0
1
Order By: Relevance
“…Osumanu [16] also found a similar prevalence rate (57.5%) of diarrhoea among under-five years children from indigenous residential areas in the Tamale Metropolis of Ghana. Most recently, in the Volta Region of Ghana, diarrhoea prevalence rate of 44.7-59.2% was reported for intervention and control groups in a randomised trial [41]. It is worth noting that our sample was younger than the GDHS sample and younger children are more vulnerable to infections and poor health, which may also be related to poor care and dietary inadequacies and may also partly explain the high diarrhoea prevalence.…”
Section: Discussionmentioning
confidence: 76%
“…Osumanu [16] also found a similar prevalence rate (57.5%) of diarrhoea among under-five years children from indigenous residential areas in the Tamale Metropolis of Ghana. Most recently, in the Volta Region of Ghana, diarrhoea prevalence rate of 44.7-59.2% was reported for intervention and control groups in a randomised trial [41]. It is worth noting that our sample was younger than the GDHS sample and younger children are more vulnerable to infections and poor health, which may also be related to poor care and dietary inadequacies and may also partly explain the high diarrhoea prevalence.…”
Section: Discussionmentioning
confidence: 76%
“…Majority of the participants could not afford water treatment products hence they drank untreated water from the river or unprotected dug wells. Previous studies have shown that covered water sources and treatment of water before consumption reduces the likelihood diarrheal diseases [2,[17][18][19] Although participants were able to link drinking untreated water and diseases, they had poor knowledge on transmission routes of schistosomiasis. Majority of the individuals interviewed believed that one can get infected with diarrhea and schistosomiasis by drinking contaminated water.…”
Section: Discussionmentioning
confidence: 99%
“…Improved water supply is one of the factors linked to reduction in episodes of diarrhoea. 21 It has been proven that households with improved water supply could reduce incidence of diarrhoea among under-five children in sub-Saharan Africa. 21 The use of pipe-borne water supply within a private household or yard is a major source of improved water supply.…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been proven that households with improved water supply could reduce incidence of diarrhoea among under-five children in sub-Saharan Africa. 21 The use of pipe-borne water supply within a private household or yard is a major source of improved water supply. Other improved drinking water sources are public water taps, protected deep well, boreholes, collected rainwater and protected springs.…”
Section: Discussionmentioning
confidence: 99%